Multiple axillary-infraclavicular lymph node metastasis from malignant rhabdoid tumor of unknown primary site - Demir, Hacı Ahmet; Kaçar, Ayper; Emir, Suna; Cihan, Birsen Songül; Tunç, Bahattin (The Turkish Journal of Pediatrics, 2012)
Malignant rhabdoid tumors (MRT) mostly originate from the kidney and central nervous system. However, they may also originate from retroperitoneal and paravertebral regions, mediastinum, liver, chest wall, extremity, and neck, as well as from the soft tissues. The most important method in the differential diagnosis is the analysis of cytogenetic alterations in the INI1 gene. A six-month-old girl presented with multiple conglomerated lymphadenopathies located in the anterior axillary line. MRT diagnosis was confirmed by loss of INI1 expression in the tumor tissue. This is the first case in the literature with unknown primary focus diagnosed from lymph node metastasis.